1998
DOI: 10.1037/0022-3514.74.6.1619
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of self-handicapping: Effects on coping, academic performance, and adjustment.

Abstract: Self-handicappers erect impediments to performance to protect their self-esteem. The impediments may interfere with the ability to do well and, as such, may result in poor adjustment. Using a longitudinal design, the present studies examined prospective effects of self-handicapping on coping, academic performance, and several adjustment-related variables (e.g., self-esteem). It was found that, compared to low self-handicappers, high self-handicappers reported higher usage of coping strategies implying withdraw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
125
1
17

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(162 citation statements)
references
References 37 publications
11
125
1
17
Order By: Relevance
“…This supports the propositions made in the CIC theory that color affects behavioral and cognitive processes in a subtle way. The results are also in line with research that has demonstrated that avoidance motivation in achievement settings evokes anxiety, task distraction, and a number of self-protective processes (e.g., disidentification, self-handicapping; Birney et al, 1969;Elliot & Church, 2003;Elliot & McGregor, 2001;Hembree, 1988;Osborne, 1995;Zuckerman et al, 1998) that negatively influence performance on tasks requiring flexible mental manipulation. In addition, these findings can also explain red-induced improved performance in tasks that require a local attentional processing style (see Mehta & Zhu, 2009).…”
Section: Color In the Achievement Context In Humans 14supporting
confidence: 88%
See 1 more Smart Citation
“…This supports the propositions made in the CIC theory that color affects behavioral and cognitive processes in a subtle way. The results are also in line with research that has demonstrated that avoidance motivation in achievement settings evokes anxiety, task distraction, and a number of self-protective processes (e.g., disidentification, self-handicapping; Birney et al, 1969;Elliot & Church, 2003;Elliot & McGregor, 2001;Hembree, 1988;Osborne, 1995;Zuckerman et al, 1998) that negatively influence performance on tasks requiring flexible mental manipulation. In addition, these findings can also explain red-induced improved performance in tasks that require a local attentional processing style (see Mehta & Zhu, 2009).…”
Section: Color In the Achievement Context In Humans 14supporting
confidence: 88%
“…In humans, encountering a negative object, event, or possibility, including the possibility of failure, is known to automatically evoke a motivational tendency to avoid that object, event, or possibility (Bargh & Chartrand, 1999;Cacioppo, Gardner, & Berntson, 1999). In addition, research has demonstrated that avoidance motivation in achievement settings evokes anxiety, task distraction, and a number of self-protective processes (e.g., disidentification, selfhandicapping; Birney, Burdick, & Teevan, 1969;Elliot & Church, 2003;Elliot & McGregor, 1999;Hembree, 1988;Osborne, 1995;Zuckerman, Kieffer, & Knee, 1998) that negatively influence performance on tasks requiring flexible mental manipulation (i.e., tasks commonly encountered at school and work). Accordingly, viewing red in an achievement context is posited to impair performance attainment because it evokes avoidance, which in turn, is inimical to performance.…”
Section: Use Policymentioning
confidence: 99%
“…A tendency to self-handicap has been shown to be associated with low self-worth, approval-seeking tendencies, personal performanceavoidance goals, and low achievement (for a review, see Urdan & Midgley, 2001). It appears that the short-term benefits situational self-handicapping may provide (e.g., transient sense of control, protected public image) are nevertheless likely to transform into long-term loss (Zuckerman, Kieffer, & Knee, 1998).…”
Section: The Present Studymentioning
confidence: 99%
“…A tendency to self-handicap has been shown to be associated with low self-worth, approval-seeking tendencies, personal performanceavoidance goals, and low achievement (for a review, see Urdan & Midgley, 2001). It appears that the short-term benefits situational self-handicapping may provide (e.g., transient sense of control, protected public image) are nevertheless likely to transform into long-term loss (Zuckerman, Kieffer, & Knee, 1998).Based on the above brief review of relevant constructs, it was assumed that the instructional context will indeed matter and that most effects are moderated by different NIEMIVIRTA 256 goal orientation preferences. Accordingly, the following main hypotheses were made: H1a: Students in the ego-involving condition will display lower levels of interest and higher levels of test anxiety than do students in the task-involving condition.…”
mentioning
confidence: 99%
“…Eğitim sürecinde, kendini engellemenin güdülenme ve başarı üzerinde olumsuz etkiye sahip olduğu belirtilmektedir (Martin, Marsh, & Debus, 2003;Zuckerman, Kieffer & Knee, 1998).…”
Section: Introductionunclassified